A mine double-order grouting material system based on opposite charge interface directional mineralization and a grouting method and application thereof
Patent Information
- Application Number
- CN202610878322.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-17
- Publication Date
- 2026-08-18
AI Technical Summary
上述路线仍主要依赖浆体整体组成优化,未解决“主体浆液需保持稳定可注、到达裂隙壁后又需快速富集粘结”的空间矛盾
1)以界面电荷和注入顺序作为可测量、可控制的技术特征,区别于常规“水泥+掺合料+纳米组分”的单浆配方优化路线;
Smart Images

Figure CN122586461A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of grouting reinforcement technology for fractured coal and rock masses in coal mines, and specifically relates to a dual-sequence grouting material system for mining based on directional mineralization of opposite charge interfaces, its grouting method, and its application. Background Technology
[0002] Fractured coal and rock masses typically exhibit a combination of problems, including fine fractures, poor connectivity, insufficient wettability of the coal and rock surface, and easy debonding at the interface after slurry solidification. Increasing the solid content of the slurry or shortening the setting time is beneficial for strength formation but can easily lead to slurry blockage near the inlet; reducing viscosity and particle size is beneficial for deep penetration but may result in insufficient effective cementitious components at the interface.
[0003] Existing inorganic composite grouting materials for mining mostly utilize ultrafine cement, fly ash, microsilica, nano-silica, carbon nanotubes, water-reducing agents, and quick-setting agents for particle size distribution or reinforcement. For example, application publication number CN114956771A discloses an inorganic composite grouting reinforcement material for mining containing modified carbon nanotubes embedded with silica, with its technical focus on the filling and reinforcement of the stone mass by the nanocomposite material. However, this approach still primarily relies on optimizing the overall composition of the grout, failing to resolve the spatial contradiction of "the main grout needing to remain stable and injectable, while also needing to rapidly enrich and bond upon reaching the fracture wall." Summary of the Invention
[0004] The technical problem to be solved by the present invention is to provide a mining dual-sequence grouting material based on the directional mineralization of opposite charge interfaces. By using an inorganic system of opposite charges injected sequentially, the interface enrichment and mineralization are triggered in situ on the fracture wall, while maintaining the injectability of the main grout.
[0005] To achieve the above objectives, the present invention employs the following technical solution: A dual-sequence grouting material system for mining based on directional mineralization at opposite charge interfaces includes independently packaged interface activation precursor liquid A and micro-nano inorganic main grout B, which are injected sequentially during use. Interface activation precursor liquid A is composed of cationic inorganic nano-sol and water. The cationic inorganic nano-sol is at least one of boehmite sol and alumina sol. At 20°C and the actual construction concentration, the zeta potential of interface activation precursor liquid A is +15mV to +50mV. The micro-nano inorganic main grout B is composed of ultrafine cement, active mineral admixtures, anionic silica sol, inorganic dispersant, and water. At 20°C and the actual construction concentration, the zeta potential of micro-nano inorganic main grout B is -10mV to -45mV. During construction, interface activation precursor liquid A is injected first, allowing it to adsorb onto the coal and rock fracture walls to form a positively charged interface activation layer. Then, micro-nano inorganic main grout B is injected, causing aggregation and solidification at the positively charged interface activation layer.
[0006] Furthermore, by weight, the interface activation precursor solution A comprises 5-20 parts of cationic inorganic nanosol with a solid content of 10%-25% and 80-95 parts of water; the pH value of the interface activation precursor solution A is 3.5-6.0, and the particle size D50 of the cationic inorganic nanosol is 10nm-80nm.
[0007] Furthermore, based on a total weight of 100 parts of cementitious materials, the micro-nano inorganic main slurry B includes: 55-75 parts of ultrafine cement, 10-25 parts of slag powder, 5-15 parts of metakaolin, 2-8 parts of anionic silica sol by solids, 0.1-0.8 parts of inorganic dispersant, and 0-4 parts of inorganic quick-setting agent; the water-cement ratio is 0.60-1.00.
[0008] Furthermore, the inorganic dispersant is selected from one or a combination of sodium hexametaphosphate and sodium pyrophosphate; the particle size D50 of the anionic silica sol is 10nm to 50nm; and the particle size D90 of the ultrafine cement is not greater than 15μm.
[0009] Furthermore, the interface activation precursor solution A and the micro / nano inorganic main slurry B are not mixed beforehand, and their injection volume ratio is 0.05:1 to 0.25:1.
[0010] A grouting method for the above-mentioned dual-sequence grouting material system for mining includes the following steps: S1: Drill grouting holes for the target fractured coal and rock mass and surrounding rock, and use clean water or compressed air to clean the grouting holes and the cracks around the hole opening; S2: Introduce the first grouting pressure and continuously inject the interface activation precursor liquid A into the grouting hole, so that the precursor liquid can fully migrate along the crack and be adsorbed on the surface of the crack wall. S3: Stop grouting and let it stand for 30 seconds to 10 minutes to ensure that the precursor liquid is fully adsorbed and forms a film; S4: Inject the micro-nano inorganic main grout B by introducing the second grouting pressure. The second grouting pressure is not lower than the first grouting pressure. The main grout accumulates and solidifies at the positively charged activated layer of the fracture wall. S5: When the grouting pressure reaches the design final pressure, or the cumulative grout injection volume reaches the design value, stop grouting, seal the grouting hole and allow it to cure naturally.
[0011] Furthermore, the first grouting pressure is 0.2MPa to 1.5MPa, the second grouting pressure is 0.5MPa to 3.0MPa, and the second grouting pressure is 1.2 to 3.0 times the first grouting pressure.
[0012] Furthermore, the switching node from step S2 to S3 can be determined by monitoring at least one of the following: return liquid conductivity, slurry pH value, and real-time slurry injection volume.
[0013] Furthermore, after the main slurry solidifies and forms, the Al / Si atomic ratio in the range of 0–500 μm from the coal-rock interface is significantly higher than that in the main solidified body region, forming a dense interface-reinforced transition layer.
[0014] The present invention also provides the application of the above-mentioned dual-sequence grouting material system for mining, which is suitable for underground grouting and reinforcement operations in low-permeability fractured coal bodies, soft coal seam surrounding rock, and coal-rock interface areas prone to debonding.
[0015] Compared with existing technologies, the beneficial effects of this invention are: 1) Using interfacial charge and injection sequence as measurable and controllable technical features, it differs from the conventional single-slurry formulation optimization route of "cement + admixture + nano-components"; 2) The micro-nano inorganic master slurry B maintains dispersion and injectability before reaching the target interface, and then becomes locally enriched after reaching the fracture wall activated by the interface activation precursor liquid A, thus achieving spatial decoupling of penetration and bonding. 3) The interface activation layer undergoes directional nucleation and mineralization reactions with the subsequent siliceous and calcareous components, which helps to reduce the porosity and debonding defects in the coal-rock-magma interface transition zone; 4) The system uses inorganic components, which are suitable for the requirements of flame retardancy and long-term durability in underground coal mines; 5) A complete chain of evidence for the effect can be established through indicators such as zeta potential, interfacial element enrichment coefficient, contact angle, interfacial bonding strength and injectability.
[0016] The core concept of this invention is sequential grouting with opposite charges: the surface of coal and rock fracture walls is usually negatively charged or contains oxygen-containing functional groups. First, a positively charged interface activation precursor liquid A is injected, which adheres uniformly to the fracture wall through electrostatic adsorption and hydrogen bonding, forming a continuous positively charged interface activation layer. Subsequently, a negatively charged micro-nano inorganic main grout B is injected. Anionic silica sol and ultrafine cement particles in the main grout are attracted by electrostatics and aggregate and undergo heterogeneous coagulation at the activation layer of the fracture wall. Under the calcium ions generated by cement hydration and the alkaline environment, aluminosilicate cementitious products such as CSH and C-(A)-SH are generated, forming a dense Al-Si-Ca-rich interface transition layer. Since the two grouts are packaged separately and injected sequentially, the premature flocculation and blockage of colloids with opposite charges at the grouting pipeline and fracture entrance can be completely avoided. The main grout far from the fracture wall always maintains low viscosity and high dispersibility, and smoothly penetrates into the deep part of the micro-fractures, ultimately achieving the dual effects of deep penetration and strong interface bonding. Attached Figure Description
[0017] Figure 1 This is a schematic diagram of the mechanism of the dual-sequence grouting process of the present invention; Figure 2 The curves showing the ζ-potential changes of interface activation precursor solution A, micro-nano inorganic main slurry B, and the two after contact. Figure 3 The particle size change curves are shown for interface activation precursor solution A, micro-nano inorganic main slurry B, and the two after contact. Figure 4 SEM image of the coal-rock interface of the solidified body Figure 5 Line scan diagrams of Al, Si, and Ca elements at the coal-rock interface of the solidified body. Detailed Implementation
[0018] It should be noted that, unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. The terminology used herein in the specification is for the purpose of describing particular embodiments only and is not intended to limit the scope of the application. The reference to "embodiment" herein means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of the application. The appearance of this phrase in various places in the specification does not necessarily refer to the same embodiment, nor is it a mutually exclusive, independent, or alternative embodiment. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of this invention without inventive effort are within the scope of protection of this invention.
[0019] A dual-sequence grouting material system for mining based on directional mineralization at opposite charge interfaces includes independently packaged interface activation precursor liquid A and micro-nano inorganic main grout B, which are injected sequentially during use. The interface activation precursor liquid A is composed of cationic inorganic nano-sol and water. The cationic inorganic nano-sol is selected from at least one of boehmite sol and alumina sol. At 20℃ and the actual construction concentration, the zeta potential of the interface activation precursor liquid A is controlled between +15mV and +50mV. This precursor liquid has small particle size and low viscosity, allowing it to quickly penetrate into micro-fractures and adsorb onto the fracture walls of coal and rock, forming a stable positively charged interface activation layer. The micro-nano inorganic main grout B is composed of ultrafine cement, active mineral admixtures, anionic silica sol, inorganic dispersant, and water, with optional addition of inorganic accelerators. At 20℃ and the actual construction concentration, the zeta potential of the micro-nano inorganic main grout B is controlled between -10mV and -45mV. The micro-nano inorganic main slurry B exhibits good overall dispersibility and low viscosity, demonstrating excellent deep penetration capabilities. During construction, an interface activation precursor liquid A is first injected to form a positively charged interface activation layer on the coal and rock fracture walls. After a certain interval, the micro-nano inorganic main slurry B is then injected. The negatively charged colloids and particles of the main slurry aggregate and solidify at the activation layer due to electrostatic effects, while the micro-nano inorganic main slurry B maintains low viscosity and continues to penetrate deep into the fractures, achieving spatial decoupling between penetration performance and interface bonding performance.
[0020] By weight, the interface activation precursor solution A comprises 5-20 parts of cationic inorganic nano-sol with a solid content of 10%-25% and 80-95 parts of water; the pH value of the interface activation precursor solution A is 3.5-6.0, and the particle size D50 of the cationic inorganic nano-sol is 10nm-80nm. In the preferred embodiment, boehmite sol with a solid content of 15% is selected, and the addition amount is 10-15 parts, with the pH value of the precursor solution controlled at 4.0-5.5, resulting in the best interface activation effect.
[0021] Based on a total weight of 100 parts of cementitious materials, the micro-nano inorganic main slurry B comprises: 55-75 parts ultrafine cement, 10-25 parts slag powder, 5-15 parts metakaolin, 2-8 parts anionic silica sol (by solids), 0.1-0.8 parts inorganic dispersant, and 0-4 parts inorganic accelerator; the water-cement ratio is 0.60-1.00. The preferred ratio is: 65 parts ultrafine cement, 15 parts slag powder, 10 parts metakaolin, 5 parts anionic silica sol, 0.3 parts inorganic dispersant, and 2 parts inorganic accelerator, with a water-cement ratio of 0.75, balancing rheological properties, setting time, and mechanical strength.
[0022] The inorganic dispersant is selected from one or a combination of sodium hexametaphosphate and sodium pyrophosphate; the particle size D50 of the anionic silica sol is 10nm to 50nm; the particle size D90 of the ultrafine cement is not greater than 15μm, to ensure that the grout can be injected into micro-cracks.
[0023] The interface activation precursor solution A and the micro-nano inorganic main slurry B are not mixed beforehand, and their injection volume ratio is 0.05:1 to 0.25:1.
[0024] A grouting method for the above-mentioned dual-sequence grouting material system for mining includes the following steps: S1: Drill grouting holes for the target fractured coal and rock mass and surrounding rock, and use clean water or compressed air to clean the grouting holes and the cracks around the hole opening; S2: Introduce the first grouting pressure and continuously inject the interface activation precursor liquid A into the grouting hole, so that the precursor liquid can fully migrate along the crack and be adsorbed on the surface of the crack wall. S3: Stop grouting and let it stand for 30 seconds to 10 minutes to ensure that the precursor liquid is fully adsorbed and forms a film; S4: Inject the micro-nano inorganic main grout B by introducing the second grouting pressure. The second grouting pressure is not lower than the first grouting pressure. The main grout accumulates and solidifies at the positively charged activated layer of the fracture wall. S5: When the grouting pressure reaches the design final pressure, or the cumulative grout injection volume reaches the design value, stop grouting, seal the grouting hole and allow it to cure naturally.
[0025] The first grouting pressure is 0.2MPa to 1.5MPa, and the second grouting pressure is 0.5MPa to 3.0MPa. The second grouting pressure is 1.2 to 3.0 times that of the first grouting pressure to ensure that the main grout diffuses into the deep cracks.
[0026] The switching node from step S2 to S3 can be determined by monitoring at least one of the following: return liquid conductivity, grout pH value, and real-time grout injection volume, thereby achieving automated construction switching.
[0027] After the main slurry solidifies and forms, the Al / Si atomic ratio in the range of 0 to 500 μm from the coal-rock interface is significantly higher than that in the main solidified body area, forming a dense interface reinforcement transition layer, which effectively eliminates interface porosity and debonding defects.
[0028] Working principle: The cationic inorganic nano-sols in the interface activation precursor solution A have small particle size and low viscosity, allowing them to penetrate micro-fractures and adhere to the fracture walls of coal and rock through electrostatic adsorption, hydrogen bonding, and surface coordination, forming a positively charged interface activation layer. This step does not require the precursor solution to solidify entirely inside the fracture.
[0029] When the micro-nano inorganic main grout B subsequently enters the fracture, the negatively charged anionic silica colloids and dispersed micro-nano particles undergo heterogeneous aggregation upon approaching the positively charged interface activation layer, causing the cementitious components to preferentially deposit on the fracture wall. The Ca²⁺ produced by cement hydration and the alkaline environment further promote the formation of CSH, C-(A)-SH, or other aluminosilicate cementitious products from the silica and alumina components. Since the two grouts, A and B, are packaged separately before pumping and injection, heterogeneous aggregation mainly occurs at the target interface rather than at the pipeline or fracture inlet. (Mechanism of the dual-sequence grouting process is illustrated.) Figure 1 . Figure 2 , Figure 3 The changes in potential and particle size after contact between opposite-sign colloids are reflected: After A and B come into contact, the absolute value of the ζ potential of the mixed system decreases significantly and approaches zero potential, indicating that the neutralization of opposite charges leads to the disappearance of electrostatic repulsion, heterogeneous aggregation occurs between particles, and the particle size increases. Figure 4 , Figure 5 Characterization of elemental enrichment at the interface: A dense, needle-like / fibrous hydration product-rich interfacial mineralization transition layer exists between the coal-rock matrix and the solidified slurry. This transition layer is continuous and free of obvious defects, enhancing the interfacial bonding strength. At the coal-rock-solidified body interface, significant synergistic enrichment peaks are observed for Al, Si, and Ca.
[0030] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments.
[0031] In the examples, the zeta potential was tested at 20℃ and the actual construction concentration; the slurry viscosity was tested at 25±1℃ and a shear rate of 100s. -1 The particle size was measured 2 minutes after pulping; the particle size parameters were uniformly measured using a laser particle size analyzer.
[0032] Example 1:
[0033] 1. Preparation of interface activation precursor solution A (parts by weight): 10 parts of boehmite sol with a solid content of 15% and 90 parts of water; stir evenly and adjust the pH value to 4.0-5.5; the ζ potential of interface activation precursor solution A was detected to be +32mV and the D50 was 45nm.
[0034] 2. Preparation of micro-nano inorganic main slurry B (total cementitious materials 100 parts by weight): 65 parts ultrafine cement, 15 parts slag powder, 10 parts metakaolin, 5 parts solid metered anionic silica sol, 0.3 parts sodium hexametaphosphate, 2 parts inorganic quick-setting agent; water-cement ratio 0.75; after stirring evenly, the ζ potential of micro-nano inorganic main slurry B was measured to be -25mV, the D90 of ultrafine cement was 12μm, and the D50 of anionic silica sol was 28nm.
[0035] 3. Grouting construction: Drill grouting holes and clean them; The first grouting pressure is 0.5 MPa, and the interface activation precursor liquid A is injected, with the volume ratio of A to B being 0.10:1. Stop grouting and let stand for 2 minutes; The second grouting pressure is 1.0 MPa, into which micro-nano inorganic main grout B is injected; After the designed injection volume is reached, the well is sealed and cured.
[0036] Example 2:
[0037] To improve the degree of interface activation, the interface activation precursor solution A consists of 15 parts boehmite sol with a solid content of 15% and 85 parts water, with a pH value of 4.0 to 5.5; the injection volume ratio of A to B is adjusted to 0.15:1; the other raw material ratios and grouting process are the same as in Example 1.
[0038] Example 3:
[0039] The low-viscosity deep penetration system uses a micro-nano inorganic main slurry B formulation (100 parts of cementitious materials): 60 parts ultrafine cement, 20 parts slag powder, 10 parts metakaolin, 4 parts solid metered anionic silica sol, and 0.4 parts sodium hexametaphosphate; the water-cement ratio is 0.90; the remaining precursor liquid formulation and grouting process are the same as in Example 1.
[0040] Comparative Example 1: Only the micro-nano inorganic main slurry B from Example 1 was injected, without injecting the interface activation precursor solution A; Comparative Example 2: The interface activation precursor solution A and the micro-nano inorganic main slurry B from Example 1 were premixed in equal amounts and then injected in one go; Comparative Example 3: Traditional ultrafine cement + mineral admixture + nano silica single slurry grouting system; Comparative Example 4: First inject deionized water, then inject the micro-nano inorganic main slurry B from Example 1.
[0041] The performance test results were conducted according to a unified testing standard, examining the zeta potential, slurry viscosity, crack propagation distance, interfacial bond strength, compressive strength, Al / Si enrichment coefficient, and contact angle reduction for each embodiment and comparative example. The results are shown in the table below:
[0042] The test data shows that the slurry in each embodiment of the present invention maintains a low viscosity and has good penetration ability; the interfacial bonding strength, element enrichment coefficient and surface wettability are all far superior to those of the comparative examples; the viscosity of the slurry in the premixed scheme (comparative example 2) increases sharply and the crack diffusion distance is shortened significantly, proving that the two liquids cannot be mixed in advance and sequential injection is a necessary technical feature of this scheme.
[0043] Detailed Explanation of the Implementation Methods: The selection of raw materials and parameter ranges in this invention can be flexibly adjusted according to the width of coal and rock fractures and the degree of surrounding rock fragmentation on site. For extremely fine fractures, smaller particle size nano-sols can be used, and the water-cement ratio can be increased to reduce slurry viscosity. For areas with severe surrounding rock fragmentation and high risk of interface debonding, the dosage and injection ratio of interface activation precursor liquid A can be appropriately increased to enhance the interface activation effect. The settling interval and grouting pressure in the grouting process of this invention can be finely adjusted according to the underground working conditions. As long as they fall within the parameter range defined by this invention, the technical effects of this invention can be achieved.
[0044] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A dual-order grouting material system for mining based on directional mineralization at opposite charge interfaces, characterized in that, The system comprises two separately packaged components, an interface activation precursor solution A and a micro-nano inorganic main slurry B, which are injected sequentially during use. The interface activation precursor solution A is composed of cationic inorganic nano-sol and water. The cationic inorganic nano-sol is at least one of boehmite sol and alumina sol. At 20°C and the actual construction concentration, the zeta potential of the precursor solution A is +15mV to +50mV. The micro-nano inorganic main slurry B is composed of ultrafine cement, active mineral admixtures, anionic silica sol, inorganic dispersant, and water. At 20°C and the actual construction concentration, the zeta potential of the main slurry B is -10mV to -45mV. During construction, the interface activation precursor solution A is injected first, allowing it to adsorb onto the coal and rock fracture walls to form a positively charged interface activation layer. Then, the micro-nano inorganic main slurry B is injected, where aggregation and solidification occur at the positively charged interface activation layer.
2. The mining dual-sequence grouting material system according to claim 1, characterized in that, By weight, the interface activation precursor solution A comprises: 5-20 parts of cationic inorganic nanosol with a solid content of 10%-25% and 80-95 parts of water; the pH value of the interface activation precursor solution A is 3.5-6.0, and the particle size D50 of the cationic inorganic nanosol is 10nm-80nm.
3. The mining dual-sequence grouting material system according to claim 1, characterized in that, Based on a total weight of 100 parts of cementitious materials, the micro-nano inorganic main slurry B comprises: 55-75 parts of ultrafine cement, 10-25 parts of slag powder, 5-15 parts of metakaolin, 2-8 parts of anionic silica sol by solids, 0.1-0.8 parts of inorganic dispersant, and 0-4 parts of inorganic quick-setting agent; the water-cement ratio of the main slurry B is 0.60-1.
00.
4. The mining dual-sequence grouting material system according to claim 1, characterized in that, The inorganic dispersant is one or a combination of sodium hexametaphosphate and sodium pyrophosphate; the particle size D50 of the anionic silica sol is 10nm to 50nm; and the particle size D90 of the ultrafine cement is not greater than 15μm.
5. The mining dual-sequence grouting material system according to claim 1, characterized in that, The injection volume ratio of the interface activation precursor liquid A to the micro-nano inorganic main slurry B is 0.05:1 to 0.25:1, and the two are not mixed beforehand.
6. A grouting method based on the mining dual-sequence grouting material system according to any one of claims 1 to 5, characterized in that, Includes the following steps: S1: Drill grouting holes for the coal and rock mass to be reinforced, and clean the grouting holes; S2: Inject the interface activation precursor liquid A into the grouting hole at the first grouting pressure, so that the precursor liquid A migrates along the coal and rock fissures and is adsorbed on the surface of the fissure wall. S3: Stop grouting and let stand for 30 seconds to 10 minutes; S4: Inject micro-nano inorganic main grout B at the second grouting pressure, the second grouting pressure being no less than the first grouting pressure, and the main grout B accumulating and solidifying at the positively charged interface activation layer of the fracture wall. S5: When the grouting pressure reaches the design final pressure or the grout injection volume reaches the design value, stop grouting and seal the hole for curing.
7. The grouting method according to claim 6, characterized in that, The first grouting pressure is 0.2MPa to 1.5MPa, the second grouting pressure is 0.5MPa to 3.0MPa, and the second grouting pressure is 1.2 to 3.0 times the first grouting pressure.
8. The grouting method according to claim 6, characterized in that, The criteria for switching from step S2 to step S3 are at least one of the following: return liquid conductivity, slurry pH value, and slurry injection volume.
9. The grouting method according to claim 6, characterized in that, After the main slurry B solidifies, the Al / Si atomic ratio in the 0-500μm region near the coal-rock interface is higher than that in the main solidified body region, forming an interface-reinforced transition layer.
10. The application of the mining dual-sequence grouting material system according to any one of claims 1 to 5, characterized in that, The grouting material system is applied to grouting reinforcement operations in low-permeability fractured coal bodies, soft coal seam surrounding rock, and areas prone to debonding at the coal-rock interface.